Behind the rules: XP experiences - CLARKE, SIOBHAN (IEEE, 2004)
Agile processes such as XP (extreme programming) have been recognised for their potential benefits of improving software. During adoption of the XP process, teams can misapply the XP principles by following them verbatim, ignoring the context in which they are applied. In this paper we document our experiences where naive applications of XP principles were altered in recognition of context. We detail our observations of how teams "looked behind" the rules and began fitting XP to the problem rather than attempting to fit the problem to XP. We conclude by reflectively focusing on how this transformation occurred and suggest that it is buying into the XP ethos that drives this change of perspective on the XP process and principles.
IEEE Agile Development Conference: 2004
PUBLISHED
Keywords: extreme programming; XP